HARMONISASI HAK PEMANFAATAN SUMBER DAYA ALAM OLEH MASYARAKAT ADAT DALAM SISTEM HUKUM INDONESIA - Setiawati, Yunia Indah (Department of Constitutional and Administrative Law, Faculty of Law Universitas Negeri Semarang (UNNES)., 2018)
The problem of natural resources aspects involving the indigenous people with the goverments and stakeholders become more sorious. The indigenous people?s position as the minority groups frequently experiencing suppression as the effect of the inforcement of a legislation. Some laws governing the natural resources and communal rights of the indigenous people are not compliance with UUPA as the main law governing the natural resources. According to the facts above, the writer conducted a research using the theory of law harmonization to find the point of problems with the aim of making it easier for the goverments to fix what should be fixed. This normative juridicial research used the method of data collection such as library reserach with the main sources were literature materials and used the research approecher such as statue approach and anality approach. The result of research indicated that there were law disharmony and inconsistent norm toward UUPA because it did not fully elaborated the contains. Many norms overtapped and potentially excluded the communal rights of the indigenous people in using the natural resources were still extremely weak and it caused material and immaterial losses for them.